2011
DOI: 10.1128/jcm.00552-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Preincubation of Blood Cultures at 37°C

Abstract: The effect of immediate incubation of blood cultures at 37°C on the turnaround time and the impact of Gram stain results on antimicrobial management were investigated. During a 6-month period, blood cultures collected at the emergency department outside laboratory operating hours were preincubated at 37°C until transportation to the laboratory. Upon the arrival of blood cultures at the laboratory, Gram stains and subcultures were made from all bottles prior to further incubation in the automated system (Bactec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…In clinical operative settings some previous studies on pre-analytical conditions and length and their effects on the time occurring for a microbiological diagnosis have been performed [1415, 3335]. None of these investigations looked at microorganism recovery or at changes in the probability of positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical operative settings some previous studies on pre-analytical conditions and length and their effects on the time occurring for a microbiological diagnosis have been performed [1415, 3335]. None of these investigations looked at microorganism recovery or at changes in the probability of positive results.…”
Section: Discussionmentioning
confidence: 99%
“…These delays can occur both at the patient's bedside and in the laboratory. Kerremans et al [28, 29] and van der Velden et al [30] demonstrated in a series of elegant studies that incubation delays for almost half of all blood cultures exceeded 4 hours (including median transport times of 3.9h and 16.0h for specimens from the ICU and Emergency Department, respectively), preincubation at the collection site significantly reduced the time to detection of positive cultures, and this resulted in more rapid adjustment of antibiotic therapy. Although blood culture instruments are rarely used outside the clinical lab, the installation of such instruments proximate to ICUs should be considered in high volume settings where transport delays are likely.…”
Section: Evolution Of Conventional Blood Culturementioning
confidence: 99%
“…considered to avoid false negatives [7], although this procedure requires significant laboratory resources. In a previous study [6], Although this study has several limitations, we may conclude that collecting adequate blood volume is critical to reduce TTD and that there is the significant benefit of receiving earlier final reports when preincubating the bottles at 37 o C when delayed entry is inevitable.…”
Section: Discussionmentioning
confidence: 99%